Secrecy precoding in MIMOME wireless communication system under partial CSI. Issue 13 (1st August 2020) - Dong, Runze; Wang, Buhong; Cao, Kunrui; Li, Xia
Abstract : In this study, a precoding scheme which is called singular value decomposition and null space (SVDNS) based scheme is proposed to enhance physical layer security of a multiple‐input multiple‐output multiantenna eavesdropper (MIMOME) system. Under the partial channel state information (CSI) of the eavesdropper, the precoding matrix for the information bearing signal is constructed firstly via SVDNS‐based scheme to acquire a compromise between improving performance of the main channel and impairing that of the wiretap channel. Then the optimal power allocation over subchannels formed by precoding matrix is obtained through solving the secrecy rate maximise problem to further improve secrecy performance. After that, under the scenario that CSI of the wiretap channel is less knowable, precoding matrix for artificial noise (AN) is proposed via SVDNS‐based scheme, and then the optimal power allocation between the information bearing signal and AN is obtained while optimal power allocation over subchannels is solved subsequently. Simulation results show that the SVDNS‐based scheme with optimal power allocation achieves a higher secrecy rate than the existing schemes, and the SVDNS‐based scheme with AN aiding could make up for the performance degradation of it without AN in the situation that CSI of the wiretap channel is more unknowable.